The Influence of Dance Utilization Kabeloa Ethnoscience-Based on Learning Outcomes of Dance Arts Subjects in Class V SDN 22 Palu - Jaya, Christiadi; Dewi, Andi Imrah; Hariana, Kadek; Zulnuraini, Zulnuraini; Pratama, Ryan Andhika (Journal of Educational Sciences, 2025)
This study aims to find out whether there is an effect of the use  of ethnoscience-based Kabeloa  dance on the learning outcomes of Dance Arts subjects in grade V of SDN 22 Palu. This research method uses a quasi-experimental research method. In this study, there are two groups that will be studied, namely the first group with treatment using the ethnoscience approach method (X1) and the other group with treatment using conventional methods (X2). The instrument of this research is a learning outcome test in the form of 15 multiple-choice questions. Data were analyzed using SPSS to find out the significant achievements between the two groups, the experimental group used the ethnoscience approach method while the control class used the conventional method. Based on the significant value  of the Independent Sample T-test is 0.000, with a significant value of the T-test < 0.05 (0.000 < 0.05) and a significant level of 5% (0.05), then Ha is accepted and Ho is rejected. So it can be concluded that there is an influence of the use of ethnoscience-based Kabeloa dance  on the learning outcomes of Dance Arts subjects in grade V of SDN 22 Palu.